"A more dreadful punishment Draco himself could not devise": Loss of Caste in Anglo-Indian Fiction, 1790–1823. Issue 2 (4th March 2021) - Soni, Samir M.
ABSTRACT: In response to the activities of the Baptist and Church Missionary Societies in India, British representations of Hindu loss of caste, a supposed consequence of Christian conversion, increased in the early nineteenth century. Loss of caste, or Brahmanical excommunication, entailed a denial of family, occupation, and/or social standing among Hindus. In British discourse near the turn of the century, it transformed from a reason to prevent missions to East India Company territories into evidence for the barbarism of Hinduism, and therefore a justification for conversion. This article supplies a much-needed investigation of its importance to fictions of the British Empire. By considering loss of caste in Jacques-Henri Bernardin de Saint-Pierre's The Indian Cottage (1791), Marianna Starke's The Widow of Malabar (1796), Robert Southey's The Curse of Kehama (1810), Mary Martha Sherwood's Indian novellas, and Sydney Owenson's The Missionary (1811), this article demonstrates that loss of caste, like sati, was both a narratological trope that routinely portrayed Hinduism as severe and a significant political issue that may have helped facilitate the utilitarian shift in British colonialism near the turn of the century.